THE ANALYSIS OF ABNORMAL RETURNS AND TRADING VOLUME ACTIVITY BEFORE AND AFTER SIMULTANEOUS GENERAL ELECTION IN THE YEAR 2019 (STUDY OF STOCKS THAT ARE INCLUDED IN THE JAKARTA ISLAMIC INDEX) - Niki Aulia Dewi; Lukman Effendy; Indria Puspitasari Lenap (Jurnal Riset Mahasiswa Akuntansi, 2021)
Political events are one of the factors that influence a country’s economic conditions. The capital market as an economic instrument cannot be separated from various environmental influences, both economic and non economic environment. The aim of the research is to find out the difference of abnormal return and trading volume activity between 10 days before and 10 days after Simultaneous General Election 2019 on the stocks included in the Jakarta Islamic Index. The sampling method in this study was conducted using saturated samples of 30 companies. Statistical analysis method used is Paired Sample T-Test and Wilcoxon Signed Ranks Test. The result of statistical test shows that variabel abnormal return and trading volume activity produce the conclution that there is no difference in abnormal return and trading volume activity between 10 days before and 10 days after Simultaneous General Election 2019 on the stocks included in the Jakarta Islamic Index. The implications of this study for issuers do not need to worry about Simultaneous General Election information because the event does not significantly influence on abnormal return and trading volume activity.